Neoclassical realism and the crisis of the realist paradigm in contemporary international relations (Economic and Political Thought, 2017)
The article refers to the crisis of realism after the end of the cold war. Itconsiders neoclassical realism as a promising theoretical attitude to revivethe realist paradigm in the post cold-war bipolar international reality. Thepaper appreciates neoclassical realism’s return to a multifaceted conceptof power present in Hans Morgenthau’s theoretical considerations and itsacceptance of the importance of domestic variables developing the powerof the state. Nevertheless, neoclassical realism is not a simple “return toMorgenthau”. It still emphasises the impact of systemic determinants andaspires more to a synthesis of classical and structural streams of realism. Thearticle indicates that the idea of the synthesis contributes to some ambiguitiesin neoclassical realism’s assumptions, especially in the methodologicalcontext. Besides, neoclassical stream suffers some internal inconsistenciesas a theoretical approach. Thus, neoclassical realism’s ability to revive realismin the post-cold war international relations is still disputable and theapproach needs some more efforts to clarify and harmonize its theoreticalassumptions.